(untitled) (Bangladesh Journal of Pharmacology, 2025)
In this study, an alternative approach to activity-based screening was employed to identify potential anti-cancer agent against colon cancer. As a result, Paeonia obovata was selected, and an active compound was isolated from its methanol extracts. Through structural and physicochemical analyses, the compound was identified as paeonenoide C, a triterpenoid. Various cell-based assays, including the MTT reduction assay, LDH release assay, and colony formation assay were conducted to assess its anti-cancer properties. Paeonenoide C exhibited cytotoxic effects in HT-29 human colon cancer cells at concentrations above 150 μM. Western blot analysis demonstrated that paeonenoide C-induced cell cycle arrest and apoptosis by suppressing the phosphorylation of retinoblastoma protein and extracellular signal-regulated kinases 1/2 while down-regulating extracellular signal-regulated kinases 1/2 expression. These findings suggest that paeonenoide C possesses potential anti-cancer activity against colon cancer cell lines.